PENGARUH KUALITAS AUDIT TERHADAP KECENDERUNGAN PERUBAHAN PERILAKU MANAJEMEN LABA: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Kurniawati Kurniawati (Jurnal Akuntansi Bisnis, 2018)
The improvement of International Financial Reporting Standard (IFRS) may narrow the chance of discretionary accrual earnings management. As a result, there will be changes in the behavior of earnings management from accrual to real earnings management. The aims of this research are to investigate the influence of audit quality on the changes of earnings management behavior from accrual to real earnings management. This research emphasizes audit quality in competency and independency through audit firm tenure and audit firm rotation  The sample used in this research were manufacturing companies listed at Indonesia Stock Exchange 2012-2015. Samples are collected by purposive sampling and resulted in 58 firms as the final sample. This research used quadratic model to investigate the relationship between audit firm tenure with real earnings management. The statistic method used was multiplied analysis multiple linear regression, with hypotheses testing of statistic t using a significance level (α) = 5%. The statistical tool used is Eviews 8. The results of this research showed that  audit firm tenure has a significant influence to the real earnings management, while audit firm rotation, firm size, and leverage has no significant influence to the real earnings management. The results also showed that audit firm tenure has concave relationship with real earnings management (convex relationship with  audit quality). This indicates that audit quality measured by audit firm tenure can decrease real earnings management in the fifth year and afterwards because the increase of audit quality through audit competence is greater than the decrease of audit independence                                                                                                                      Keywords : real earnings management, audit firm tenure, audit firm rotation, concave, convex, quadratic model